2019
DOI: 10.1186/s12884-019-2314-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the lower uterine segment in pregnant women with and without previous cesarean section in 3 T MRI

Abstract: Background Prenatal risk stratification of women with previous cesarean section (CS) by ultrasound thickness measurement of the lower uterine segment (LUS) is challenging. There is a wide range of proposed cutoff values and a valuable algorithm for selection before birth is not available. Using 3 T magnetic resonance imaging (MRI), we aimed to identify possible shortcomings of the current protocols used for birth selection after CS. Therefore, we evaluated anatomic and morphologic differences of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…46,47 In addition, myometrial thinning is often seen in advancing gestation and can be more pronounced in women with previous cesarean delivery. 58 This marker can be iatrogenically produced and/or exaggerated with undue transducer pressure, highlighting the need to minimize transducer pressure on the abdomen when examining the placenta. 41,46 Uterovesical interface Uterovesical interface markers include bridging vessels, increased vascularity between the uterus and bladder, and interruption of the bladder wall.…”
Section: Uteroplacental Interfacementioning
confidence: 99%
“…46,47 In addition, myometrial thinning is often seen in advancing gestation and can be more pronounced in women with previous cesarean delivery. 58 This marker can be iatrogenically produced and/or exaggerated with undue transducer pressure, highlighting the need to minimize transducer pressure on the abdomen when examining the placenta. 41,46 Uterovesical interface Uterovesical interface markers include bridging vessels, increased vascularity between the uterus and bladder, and interruption of the bladder wall.…”
Section: Uteroplacental Interfacementioning
confidence: 99%
“…Further studies must also consider the quality of cesarean scar [70], as equal myometrial thickness could be associated with different scar strength and viability; in fact, it is conceivable that a uterine scar from a doublelayer closure is less prone to all the obstetrical complications than a uterine scar from a single-layer closure, regardless of their respective HR. In this regard, it should be mentioned that a study comparing the thickness of the lower uterine segment in a patient with and without a previous CS showed that 23% of women without a previous CS had a lower uterine segment thinning up to 1 mm on magnetic resonance imaging [71].…”
Section: Discussionmentioning
confidence: 99%
“…MRI, a biological magnetic spin imaging technique, uses the characteristics of spin motion of the nucleus and generates a signal within the external magnetic field after being excited by radiofrequency pulses, then the signal is detected and entered into a computer for processing and transforming into images on-screen. As a multiplanar and multisequence imaging, the MRI has the characteristics such as high spatial resolution, high soft-tissue resolution, and high blood flow sensitivity, and can clearly show the location of the gestational sac in the lower uterine segment and accurately measure the thickness of the gestational sac and the anterior muscular layer, which has unique advantages in assessing the relationship with pelvic visceral structures and the depth of implanted scars [ 19 ].…”
Section: Discussionmentioning
confidence: 99%